Molecular dynamics simulation of the cyclic decapeptide antibiotic, gramicidin S, in dimethyl sulfoxide solution - Mihailescu, Dan; Smith, Jeremy C. (The journal of physical chemistry. B, Biophysics, biomaterials, liquids, and soft matter, 1999)
We report on a 5 ns molecular dynamics simulation of the decapeptide antibiotic, gramicidin S (cyclo-(Leu-DPhe-Pro-Val-Orn)2) in dimethyl sulfoxide solution. Throughout the simulation the backbone ring maintains an antiparallel β-pleated sheet conformation with two type II‘ β-turns. The backbone dihedrals are relatively inflexible and do not undergo any conformational transitions. The simulation reproduces the Φ and Ψ angles derived from nuclear magnetic resonance spectroscopy to within 18° standard deviation on average. Correlations between the backbone dihedral angles are found. The side chain dihedrals are much more flexible, and the multiple conformational states of these are classified using a clustering technique. Side chain hydrogen-bonding involving the ornithine and phenylalanine residues is analyzed and discussed in the context of previous work.